La cardiotoxicité du trastuzumab chez les patientes traitées pour un cancer du sein HER 2+ - Khadroune Nour El Houda (Université Amar Telidji de Laghouat Faculté de Médecine, 2021)
Breast cancer is the most common cancer among women worldwide, its prevalence is increasing but mortality has decreased dramatically due to the growth of various cancer treatments. the protocols of the targeted therapy , which included the trastuzumab component , are indisputable in oncology and cardiac toxicity presenting the major limiting factor of its use . Our work focuses on a retrospective study conducted at the oncology department of EPH Laghouat , studying the cardiotoxicity of trastuzumab on 50 patients already infected by breast cancer HER2+. This work was conducted between January 2014 and December 2019 . The criteria included in this study touch any patient with breast cancer expressing HER2 treated by trastuzumab , with retained initial cardiac function and 55% LVEF . We have excluded patients who have history of heart diseases , who have a contraindication for trastuzumab , and who have incomplete cardiac echo record. The main of cardiac monitoring were cardiac ultrasound or isotopic ventriculography ;the toxicity criteria was those of the New York Heart Association(NYHA) ; a detailed operating chart was completed for each of our patients. The main objectif of our study was to assess the incidence of cardiotoxicity in patients with breast cancer HER2+ treated by trastuzumab. 06% of our patients had cardiotoxicity to trastuzumab (03 cases) ; two patients had an asymptomatic decrease and reversible in LVEF.And one patient had clincally significant heart failure requiring appropraite treatment for ICS and definitive dicontinuation of trastuzumab. Cardiotoxicity with trastuzumab is not common enough in our series but it does exist, which requires several careful preventive measures including monitoring by echocardiography.
121 p.